Rare bilateral corneoscleral perforation secondary to ocular tuberculosis: a case report and clinical insights - Justin Dreyer; Lauren Kiryakoza; Jonathan Tijerina; Thomas Albini; Guillermo Amescua (Journal of Ophthalmic Inflammation and Infection)
Abstract Background This case represents a rare presentation of bilateral corneoscleral perforation secondary to presumed ocular mycobacterium tuberculosis infection with the goal of reporting a case of bilateral corneoscleral perforation in the setting of a positive interferon-γ release assay (IGRA) test. Findings A 27-year-old patient presented with five months of redness, worsening eye pain, and five days of decreasing vision. Visual acuity (VA) was counting fingers bilaterally. Intraocular pressure (IOP) was 10 mmHg and 19 mmHg in the right and left eye, respectively. A slit lamp examination disclosed conjunctival injection, corneal haze, bilateral mutton-fat keratic precipitates, and a hypopyon in both eyes. The right eye had a 1.5 mm × 1.5 mm Seidel-positive corneal perforation with uveal prolapse. Similarly, the left eye had a 0.5 mm × 0.5 mm Seidel-negative inferior corneal perforation with uveal plugging. The chest X-ray showed a left-sided pleural effusion. Conclusion Computed tomography (CT) of the face and sinuses showed bilateral circumferential globe thickening. IGRA was positive. All other rheumatologic and infectious workups were negative, including HIV, ACE, ANA, ANCA, CRP, anti-scleroderma antibody and HCV. The patient was treated with intravenous methylprednisolone and seven months of rifampin, isoniazid, pyrazinamide, and ethambutol. This workup shows the rare bilateral corneal involvement of ocular tuberculosis.